Effect of thermosonication on functional and rheological properties of green lentil protein - Baskinci, Tuğba; Amanda Apud, Dea Amalia; Gül, Osman (International Society of Academicians, 2021)
The objective of this study was evaluate the effect of ultrasound in bath at 30, 50 and 70oC for 5, 10, 20 and 30 min for improve functional and rheological properties of green lentil protein. The percentage of recovered lentil protein after alkaline extraction was calculated as 82.79%. The protein solubility of solutions significantly increased after sonication treatment. However, sonication treatment at 70oC after 20 min caused a partial reduction of protein solubility. Thermosonication process markedly improved the emulsion activity and stability index up to 176.02 m2/g and 40.68%, respectively, and also foaming capacity of sonicated protein suspension was 3.35-fold higher than that of untreated sample. Protein suspensions displayed shear-thinning, and results were satisfactorily fitted to Ostwald-de Waele model (R2< 0.926). As a result, the findings indicated that functional and rheological properties of proteins can be improved by ultrasound in combination with heating, and thus thermosonication process may be a valuable processing technology for modify of lentil protein.
Keywords: Food Engineering; Lentil; Thermosonication; Protein isolate; Functional properties; Rheological properties; Gıda Mühendisliği